Digital image correlation for the analysis of in-plane tested unreinforced masonry walls. (February 2021) - Howlader, M.K.; Masia, M.J.; Griffith, M.C.
Abstract: In the experimental assessment of the in-plane behaviour of unreinforced masonry (URM) walls containing openings, accurate measurement of the deformations occurring in the pier and spandrel substructures is important. Eight full-scale perforated URM walls were tested under in-plane cyclic loading and constant vertical pre-compression load. To measure the deformation of the walls (pier-spandrel substructures) during testing and to capture the full-field cracking of the masonry, a two dimensional (2D) Digital Image Correlation (DIC) technique was used in parallel with traditional hard-wired instrumentation (Linear Variable Differential Transformers, commonly referred to as LVDTs for short). This paper describes the detailed procedures of using DIC in large scale masonry wall testing. Firstly, the digital images at the first peak of each displacement amplitude in both push and pull directions for one specimen were analysed using the VIC-2D software to validate the DIC results against the LVDT recorded measurements. After confirming the accuracy of the DIC measurements for the specimen, the pier-spandrel movements and the cracking analyses of all the walls were performed in order to better understand the integrity of these elements during cyclic in-plane loading.